2011
DOI: 10.1161/circinterventions.111.962555
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CYP2C19*2 and *3 Loss-of-Function Alleles on Platelet Reactivity and Adverse Clinical Events in East Asian Acute Myocardial Infarction Survivors Treated With Clopidogrel and Aspirin

Abstract: Background-As compared with whites, East Asians more often carry the cytochrome P450 (CYP) 2C19 loss-of-function (LOF) allele with the CYP2C19*3 variant. The influence of the CYP2C19 LOF alleles (*2 and *3) on clopidogrel response and clinical outcomes in East Asians with acute myocardial infarction (AMI) has not been reported. We sought to evaluate the effect of the CYP2C19 variants on clopidogrel pharmacodynamics and long-term prognosis in these patients. Methods and Results-Patients who survived an AMI (nϭ2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(81 citation statements)
references
References 45 publications
8
73
0
Order By: Relevance
“…[10][11][12][13][14] Of note, individuals carrying two LOF alleles, who are considered CYP2C19 poor metabolizers (PMs), showed the worst pharmacokinetic/pharmacodynamic profiles for clopidogrel and the highest risk of cardiovascular outcomes compared with those with one LOF allele or none. 10,13,14 Because the metabolizing enzyme and drug transporter function together instead of separately in pharmacokinetics, it may be reasonable to assume that the evaluation of both the CYP2C19 PM status and ABCB1 3435 TT might improve the ability to predict adverse clinical outcomes in patients taking clopidogrel after PCI. However, there is a paucity of data on the combined effect of these two at-risk variants.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] Of note, individuals carrying two LOF alleles, who are considered CYP2C19 poor metabolizers (PMs), showed the worst pharmacokinetic/pharmacodynamic profiles for clopidogrel and the highest risk of cardiovascular outcomes compared with those with one LOF allele or none. 10,13,14 Because the metabolizing enzyme and drug transporter function together instead of separately in pharmacokinetics, it may be reasonable to assume that the evaluation of both the CYP2C19 PM status and ABCB1 3435 TT might improve the ability to predict adverse clinical outcomes in patients taking clopidogrel after PCI. However, there is a paucity of data on the combined effect of these two at-risk variants.…”
Section: Introductionmentioning
confidence: 99%
“…CYP2C19*2 (containing a splicing defect) and CYP2C19*3 (containing a premature stop codon), are 2 major LOF alleles of CYP2C19. A recent Korean study 12 suggested that CYP2C19 LOF alleles had a gene-dose effect on post-clopidogrel platelet reactivity and that the effect of the CYP2C19*2 vs. *3 LOF allele carriage on platelet reactivity did not differ in East Asians. Additionally, there is no difference in the prevalence of HPR between CYP2C19*2/*2 and CYP2C19*2/*3 carriers.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, there is no difference in the prevalence of HPR between CYP2C19*2/*2 and CYP2C19*2/*3 carriers. 12 The fact that the magnitude of platelet reactivity increased by the presence of CYP2C19 LOF alleles encourages the search for the additional effect of CYP2C19 genotype on periprocedural outcome during PCI.…”
Section: Discussionmentioning
confidence: 99%
“…42 The percentage of patients who had undergone percutaneous coronary intervention varied from 0 to 100%, and the proportion of smokers ranged from Volume 17 | Number 1 | January 2015 | GENETIcS in MEDIcINE 8 to 56%, with three studies including more than 50% of smokers. [42][43][44] All 30 studies addressed clinical end points, and 17 studies also investigated ST. The definition of the composite clinical outcome and the event rates varied between primary studies.…”
Section: Primary Study Characteristicsmentioning
confidence: 99%